Pengaruh Kecukupan Modal pada Profitabilitas Dengan Good Corporate Goveranance Sebagai Variabel Pemoderasi - Gesaputri, Ida Ayu Bintang; Widanaputra, Anak Agung Gede Putu (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This study aims to obtain empirical evidence about the effect of capital adequacy on profitability with good corporate governance as a moderating variable. This research was conducted at banking companies listed on the Indonesia Stock Exchange in 2011-2016. The method of determining the sample used is purposive sampling. The data analysis technique used is the Moderated Regression Analysis (MRA) test. Based on the results of the study, it is known that good corporate governance is not as a moderating influence of capital adequacy on profitability. Based on the period of application of good corporate governance, it is more long-term so that success cannot be measured based on short-term profitability. The theoretical implications of research are in addition to references to further research regarding research related to capital structure theory and agency theory. On the other hand the practical implications of research are as additional information for investors before investing. Keywords: profitability, capital adequacy, and good corporate governance